The Effects on The Economy and Environment Caused By Electric Cars Compared to The Conventional Ones - Cosmin Codruț BLEDEA; Izabela Luiza POP; Rita Monica TOADER (Communications of International Proceedings, 2022)
From year to year, the environment situation is worsening at an alarming rate. Air pollution has reached record levels, which is why ozone layer have come to be seriously affected. All these aspects lead to the warming of Earth and had a negative impact on people’s health. Therefore, humanity has begun to focus more and more on remedying these adverse effects through various methods, which are more or less effective. In the case of CO2 emissions that are higher than ever, the solution is a very complex one and difficult to achieve. For this reason, various alternatives have appeared: electric cars, hybrid cars, as well as those with hydrogen, compressed natural gas and bioethanol. Since electric cars are the first choice as an alternative and they have shown a great potential, the purpose of this paper is to present whether or not this alternative is really a “greener” choice or not. To achieve this purpose, a literature review and a data analysis provided by Eurostat, U.S. Department of Energy and the Organization of the Petroleum Exporting Countries were performed. The results of this study highlight that the sustainability of the electric cars is influenced by the geographical area where they are used.
Keywords: Economy; Environment; Electric Cars; Sustainability